2020
DOI: 10.1186/s12864-020-07037-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression within the periaqueductal gray is linked to vocal behavior and early-onset parkinsonism in Pink1 knockout rats

Abstract: Background Parkinson’s disease (PD) is a degenerative disease with early-stage pathology hypothesized to manifest in brainstem regions. Vocal deficits, including soft, monotone speech, result in significant clinical and quality of life issues and are present in 90% of PD patients; yet the underlying pathology mediating these significant voice deficits is unknown. The Pink1−/− rat is a valid model of early-onset PD that presents with analogous vocal communication deficits. Previous work shows ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 72 publications
4
22
0
Order By: Relevance
“…Interestingly, deficient sensory processing has also been reported in MIA models [ 25 ]. Besides, a growing body of evidence has shown that alterations in the periaqueductal gray, a brainstem nucleus engaged in the production of vocalizations and indirect modulation (via motor neurons in the brainstem) of vocal fold vibration, may be the leading cause of impaired communication in mammals [ 48 , 49 ]. Further studies are necessary to answer whether sensory or motor dysfunctions lead to USV alterations and consequently which brain regions (ascending auditory pathway or the periaqueductal gray) are involved in the MIA-induced vocal communication impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, deficient sensory processing has also been reported in MIA models [ 25 ]. Besides, a growing body of evidence has shown that alterations in the periaqueductal gray, a brainstem nucleus engaged in the production of vocalizations and indirect modulation (via motor neurons in the brainstem) of vocal fold vibration, may be the leading cause of impaired communication in mammals [ 48 , 49 ]. Further studies are necessary to answer whether sensory or motor dysfunctions lead to USV alterations and consequently which brain regions (ascending auditory pathway or the periaqueductal gray) are involved in the MIA-induced vocal communication impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The Illumina Stranded Total RNA Library Prep Kit was used to remove rRNA and generate sequencing libraries as described by the manufacturer and in Kelm-Nelson and Gammie, 2020. 46 Sequencing was performed on an HiSeq 2000 high-throughput sequencing system within a single run (Illumina, Inc). After removal of adaptor sequences, contamination and low-quality reads, reads were mapped to the annotated rat (Rattus norvegicus) genome in Ensembl.…”
Section: Library Construction and Rna Sequencingmentioning
confidence: 99%
“…In addition, KCNJ2, APBB1, and DCTN1 genes are associated with neurodegenerative diseases [42][43][44] . The GJAS gene is related to a gene associated with PD 45 . Finally, the SETX gene is related to the tremor which is determined as a sign of PD 46 .…”
Section: /23mentioning
confidence: 99%